Etude de la production laitiere et de la croissance des veaux de vaches allaitantes N'Dama et Baoule en Cote d'Ivoire. I. Estimations des productions laitieres - Hoste, Christian H.; Cloe, L.; Deslandes, P.; Poivey, J.P. (1983)
Studies milk production and its relationship to calf growth for N'Dama and Baoule suckling cows in an improved environment. Milk production was estimated by weighing calves before and after two consecutive suckling (night and morning) once a month from birth till 7 months. Production records from 210 days were analysed. The average milk production was 413 kg for N'Dama and 356 kg for Baoule. Methodology used under-estimated milk production. Calving number and month greatly influenced milk production. The lactation curve for both breeds are very different from those observed in Europe, thus confirms that N'Dama and Baule breeds are not good milk producers. Further investigation to determine if milk quantities produced are enough to allow the calves to fully express their genetic potential is recommended.